Proceedings of the 2016 Conference on Empirical Methods in Natural Language Processing 2016
DOI: 10.18653/v1/d16-1078
|View full text |Cite
|
Sign up to set email alerts
|

Speculation and Negation Scope Detection via Convolutional Neural Networks

Abstract: Speculation and negation are important information to identify text factuality. In this paper, we propose a Convolutional Neural Network (CNN)-based model with probabilistic weighted average pooling to address speculation and negation scope detection. In particular, our CNN-based model extracts those meaningful features from various syntactic paths between the cues and the candidate tokens in both constituency and dependency parse trees. Evaluation on BioScope shows that our CNN-based model significantly outpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 17 publications
0
38
0
Order By: Relevance
“…Work by Fancellu, Lopez, and Webber (2016) and Qian et al . (2016), although not focused on the sentiment analysis domain, should be highlighted. Fancellu et al .…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Work by Fancellu, Lopez, and Webber (2016) and Qian et al . (2016), although not focused on the sentiment analysis domain, should be highlighted. Fancellu et al .…”
Section: Related Workmentioning
confidence: 99%
“…Qian et al . (2016) propose a convolutional neural network-based model with probabilistic weighted average pooling to also address negation scope detection. This system first extracts path features from syntactic trees with a convolutional layer and concatenates them with their relative positions into one feature vector, which is then fed into a soft-max layer to compute the confidence scores of its location labels.…”
Section: Related Workmentioning
confidence: 99%
“…By contrast, machine learning-based systems do not require active human expert participation to adapt to a new dataset/domain. Earlier works utilizing the statistical approaches for negation scope detection include Support Vector Machines (SVM), Conditional Random Fields based models (CRF) (Agarwal and Yu, 2010; Councill et al, 2010) as well as hybrid CRF-SVM ensemble models (Zhu et al, 2010) (Morante and Daelemans, 2009) Recently, Neural Network-based approaches have been proposed for such tasks, including Convolutional Neural Network (CNN)-based (Qian et al, 2016) and Long Short Term Memory (LSTM)-based (Fancellu et al, 2017;Sergeeva et al, 2019) models.…”
Section: Previous Workmentioning
confidence: 99%
“…Machine learning methods have been applied to cope with the negation detection task, using mainly a conditional random field (CRF) algorithm with dense vector features, such as character or word embedding [ 13 , 14 ]. More recently, deep learning approaches using recurrent neural networks (RNNs), convolutional neuronal networks (CNNs), and encoder-decoder models have also been exploited to solve this task [ 15 - 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some approaches were proposed to rely on syntactic parse information to automatically extract the most relevant features [ 51 ]. Qian et al [ 15 ] designed a CNN-based model with probabilistic weighted average pooling to address speculation and negation scope detection. Evaluation of the BioScope corpus showed that their approach achieved substantial improvement.…”
Section: Introductionmentioning
confidence: 99%